Korelasi Penguasaan Kosakata terhadap Kemampuan Menulis Puisi Kelas V Sekolah Dasar di Desa Tempur - Erna Listyaningsih; Murtono Murtono; Muhammad Noor Ahsin (Journal of Education and Culture (JEC), 2021)
The purpose of this study was to find out how big the relationship between students' vocabulary mastery and the ability to write poetry in fifth grade students in Tempur Village. This research usescorrelational quantitative research method product moment. By using a saturated sample of 39 students from class V MI Al-Anwar Tempur, SD N 02 Tempur, and SD N 03 Tempur. Data collection techniques from this study were using interview, test and documentation techniques. Data analysis used hypothesis testing and prerequisite test, namely normality test and linearity test. The results of the study were obtained from the test instrument, namely multiple choice for vocabulary mastery as many as 20 questions and a test of the ability to write poetry. then the data is processed using SPSS statistics 21. From the results of statistical calculations on the variable mastery of vocabulary, it got an average of 66.79 with a standard deviation of 16.878, while the variable of ability to write poetry got an average of 63.21 and a standard deviation of 15.832. From the results of the research analysis, it is shown that the rcount gets 0.670 with N = 39 at a significant level of 5% getting an rtable of 0.316. From these results it can be said that rcount > rtable (0.670 > 0.316). So it can be concluded that there is a relationship between students' vocabulary mastery and the ability to write poetry in fifth grade elementary school students in Tempur Village.